Records Management Practices of Micro and Small-Sized Enterprises (MSEs) In Legislative District III of Isabela - Cantor, Kurt Morin; Pascua, Dahlee (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study explored the records management practices of Micro and Small-sized Enterprises (MSEs) in Legislative District III of Isabela, focusing on the types of records managed, tools and systems used, records management procedures, perceived importance of records management, challenges encountered, and possible improvements. Using a qualitative descriptive research design, the study gathered data through semi-structured interviews from 40 purposively selected MSE owners, managers, and records custodians across the municipalities of Alicia, Angadanan, Cabatuan, Ramon, and San Mateo in Legislative District III of Isabela. The interview instrument was validated by records management experts, and the collected data were analyzed using Braun and Clarke’s thematic analysis. Findings revealed that MSEs commonly managed sales and financial, operational and inventory, and regulatory and administrative records. Most enterprises relied heavily on manual and paper-based systems, although some utilized basic digital tools such as Microsoft Excel, Google Sheets, and computerized monitoring systems. Records management practices were generally informal and inconsistent, with many enterprises lacking formal policies, standardized procedures, and structured disposal systems. Despite these limitations, respondents recognized records management as essential for operational efficiency, accountability, customer service, decision-making, and regulatory compliance. Major challenges identified included limited storage space, missing records, insufficient skills, lack of standardized systems, and limited digital integration. The study concluded that there is a strong need for standardized records management systems, digitalization, improved security measures, and continuous training programs to enhance operational efficiency and organizational sustainability among MSEs. The study aligns with Sustainable Development Goals (SDGs) 8, 9, and 16 by promoting economic growth, innovation, organizational efficiency, accountability, and stronger institutional practices.